MAJOR OUTCOMES OF THE WORK PERFORMED BY ST. PETERSBURG RESEARCH INSTITUTE OF RADIATION HYGIENE AFTER PROFESSOR P. V. RAMZAEV ON THE IMPLEMENTATION OF THE FEDERAL TARGETED PROGRAM “MITIGATION OF THE RADIATION ACCIDENTS’CONSEQUENCES UNTIL 2015” AND OF THE “JOINT ACTIVITIES PROGRAM ON MITIGATION OF THE CHERNOBYL DISASTER WITHIN THE UNION STATE FOR THE PERIOD UNTIL 2016“ - A. N. Barkovskiy; G. Ya. Bruk; A. A. Bratilova; O. S. Kravtsova (Радиационная гигиена)
The article presents major results of the work performed by St. Petersburg Research Institute of Radiation Hygiene after Professor P. V. Ramzaev on public contracts signed within the implementation of the Federal targeted program “ Mitigation of the radiation accidents’ consequences for the period until 2015” ( Direction IV “ Streamlining of monitoring systems and their elements and situation forecasting on radioactively contaminated territories paragraph 14 “The analyses and comprehensive evaluation of radiation situation changes on radioactively contaminated territories “ aimed at compilation of radioactively contaminated zones’ settlements list and Direction VI “Awareness raising and social -psychological rehabilitation of radiation- affected residents”, paragraph 20 “Creation of unified informational system on ensuring population’s radiation safety and overcoming radiation accidents’ consequences via development of the federal and regional informational resources’ systems” and “ Joint activities program on mitigation of the Chernobyl disaster within the Union State for the period until 2016” ( Direction II “ Streamlining of unified radiation protection system in radioactively contaminated territories” paragraph 2.1 “ The harmonization of requirements, methods and technologies aimed at mitigation of Russian and Belorussian population’s internal and external exposure, the development of radiation control and monitoring unified system”, sub-paragraph 2.1.1 “The development of unified assessment and forecast system for population exposure doses and rationing of radionuclide – containing foodstuffs, agricultural products and forest preserves based on the international approaches” ) over the period from 2011 to 2015.